Some Identities of Fully Degenerate Dowling Polynomials and Numbers - Lingling Luo; Yuankui Ma; Wencong Liu; Taekyun Kim (Discrete Dynamics in Nature and Society)
Recently, Kim-Kim introduced the degenerate Whitney numbers of the first and second kind involving the degenerate Dowling polynomials and numbers. In this paper, we introduce the fully degenerate Dowling polynomials and the fully degenerate Bell polynomials and derive some identities involving these polynomials. We also obtain the generating functions, expressions, and recurrence relations for the fully degenerate Dowling polynomials and the fully degenerate Bell polynomials and other special polynomials and numbers.